Impact of Digital Capability on SMEs Performance: Mediating Role of Digital Business Transformation - Dwiputra Hutama; Raharjo, Kusdi; Fahrudi, Agung Nugroho Luthfi Imam (Wacana Journal of Social and Humanity Studies, 2023)
This study aims to examine and analyze the effect of Digital Capability on Business Performance through the mediation of Digital Business Transformation. This study seeks to determine the business performance of an SME by evaluating digital business capabilities and transformation owned by SMEs in the Greater Malang area. This type of research is explanatory research with a sample of 330 UKM in the Greater Malang area, especially in the culinary, craft, and fashion fields. The sampling technique used in this study is the quota sampling technique, and the analysis method uses Structural Equation Modeling (SEM) analysis with the SmartPLS approach. The findings in this show that Digital Capability significantly influences Business Performance directly and simultaneously through the mediation of Digital Business Transformation. The limitations in this study are the existence of obstacles to access for SMEs in the Greater Malang area, which incidentally has a very large area, so it takes quite a long time, coupled with the Covid-19 pandemic that has hit Indonesia, access is constrained due to the government's social distancing policy. Keywords: SME, digital, capability, transformation, performance